PELAKSANAAN SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN DALAM PEREKAMAN KTP????E L DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN POSOPROVINSI SULAWESI TENGAH - Dedi Kusmana; Andika Nugra Deo Bermuli (Jurnal Media Birokrasi, 2020)
This study takes title ”Implementation Of Citizen Administration Information System In Recording Electronic Identity In Poso, Central Sulawesi”. This researchwas description about how the realization of KTP-el input based on Administration Information System worked in Poso. The purpose of this study was to determine the Population Administration Information System Implementation in recording the ID card-el in Poso and to determine the limiting factor Population Administration Information System Implementation in recording KTP-el in Poso. Research method the writer used was exploratory method by analyzing data through inductive approachment. As for how to collect data is by observation, interview and documentation. Based on an analysis conducted by the authors, it turns Population Administration Information System Implementation in recording KTP-el in Poso has not gone well because they wear long-Standard Operating Procedure and also still hampered by several obstacles that are still people who do not do the recording, the Internet is still often dif????icultconditions KTP-el recorders are sometimes broken. At that moment lasted, socialization Administration Information System Implementation to the public hopefully maximized followed by improving the competence of the relevant institutions about damage to goods KTP-el input based arga Administration Information System Implementation in the town of Poso could be better and the maximum. Keywords: implementation, population administration information system